Compressive strength of nanohybrid composite resin after the application of glycerin immersed in fermented milk - Sukaton, Sukaton; Prasetyo, Eric Priyo; Almira, Amanila Hena; Santiaji, Daradhasih Bestari; Sukandar, Wilson (Universitas Airlangga, 2023)
Background: The prevalence of dental caries in Indonesia in 2018 is 45.3% of the population. Tooth filling is done so that dental caries does not spread further. The restorative material that is commonly used is composite resin. The compressive strength of composite resin is affected by the polymerization process. The surface of the composite resin exposed to air causes the formation of oxygen inhibited layer (OIL). Glycerin acts as a surface coating that can inhibit contact between the composite resin and air so that polymerization can run optimally. Changes in the mechanical properties of composite resins are also influenced by salivary pH and food intake. The acid contained in fermented milk can affect the matrix and filler bonds in composite resins. Further research is needed to determine the compressive strength of nanohybrid composite resins after the application of glycerin in fermented milk immersion. Purpose: To find out whether there is a change in the compressive strength of nanohybrid composite resin after the application of glycerin immersed in fermented milk, also to find out whether the glycerin application and immersion in fermented milk play a role in causing changes of the compressive strength. Methods: Laboratory experimental research with a total sample of 28 which was divided into 4 groups. Composite resin samples were made with a thickness of 3 mm and a diameter of 5 mm, followed by measuring the compressive strength using the Universal Testing Machine. Results: Independent T-Test test showed significantly different results. The compressive strength value of the group with glycerin application was higher than without glycerin application. Meanwhile, the group immersed in fermented milk drinks had lower compressive strength compared to saline immersion. Conclusion: The compressive strength of the nanohybrid composite resin changed after the application of glycerin immersed in fermented milk.